The code breaker [compact disc, unabridged] : Jennifer Doudna, gene editing, and the future of the human race - Isaacson, Walter (Audioworks, an imprint of Simon & Schuster Audio Division, 2021)
A portrait of the Nobel Prize-winning scientist explores the impact of James Watson's "The Double Helix" on her career and how her team's invention of CRISPR technology enabled revolutionary DNA-editing approaches to fighting disease, as well as curing diseases, fending off viruses, and enhancing our children.